Pelatihan Diversifikasi Produk Olahan Susu di Sentra Peternakan Sapi Perah Kelurahan Kebon Pedes - Nurlaila Mahdiah (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Milk is a special product. This white liquid contains balanced and complete nutrients needed by the body such as protein, fat, carbohydrates, minerals, and vitamins. Milk is also the main source of nutrition for babies before they can digest solid food. The diversification of processed milk product training for the Kebon Pedes community, especially housewives, aims to increase the added value of cow's milk. Cow's milk which is sold in fresh form has properties that do not last long and are easily damaged. Because it is perishable, efforts are needed to handle milk that has been damaged or not fresh (off quality) into new products that have added value. Community service activities are carried out in Kebon Pedes Village, Tanah Sareal Regency, Bogor City on December 2019. The form of this activity is the delivery of knowledge and training on diversification of dairy cattle processed products. There are three dairy products that can be made, namely milk candy, milk bread, and chicken milk noodles. Three dairy products are products that have high nutritional value and are safe for consumption, especially for children.